Adulteration of natural honey and the nutritional effect - Radu, Steluta; Cojocaru, Elena; Cojocaru , Cristi; Lupu, Diana Elena (Progress in Nutrition, 2021)
Council Directive 2001/110 / EC (1) defines honey as the sweet natural substance produced by Apis melifera bees. Honey contains especially different types of sugars, especially fructose and glucose, as well as other substances, such as organic acids, enzymes and solid particles resulting from honey collection. It is an aqueous solution rich in sugary substances up to 80% represented mainly by glucose and fructose that come from the floral nectar, extrafloral, manna and other sources, collected by bees and stored in honeycombs. Enzymes, which the bees introduce into the nectar, have the ability to split sucrose, maltose, melezitosis, raffinose, melibiosis, this process lasting for many years. The transformation of the nectar by the bees into honey is then accompanied by the exchange and replacement of the content of useless acids, with the release of the surplus water. The pH value of the matured shoulder varies from 3,5-5.5, depending on its floristic origin. The bees feed on nectar, honey, pollen, water and for the use of larvae and quail feeds, in addition, milkweed is used. Except for the water, the honey and pollen are stored as reserves. Artificially, a wide range of food can be used in bee feed: sugar syrup and sherbet, cough sugar, powdered sugar mixed with yeast, powdered milk, delipidated soybean meal, corn pollen, various cereal flours, medicines as well as herbal supplements. From nectar, manna or sweet juices, which are found in the different parts of plants and trees, in combination with some substances that are born in the salivary glands of bees, honey is obtained, which the bees deposit in the honeycomb cells. Subsequently, the honey is stored in the honeycomb cells and left in the air for a while, for the water to evaporate. Finally, these cells are tightly sealed with some wax caps.